KONSEP IBNU KHALDUN TENTANG PRODUKSI DALAM EKONOMI ISLAM - Subaidi; Subiyanto (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2020)
Ibn Khaldun discovered many basic economic ideas in the centuriesbefore his birth “officially